Designing a multidimensional profiling framework for English learners - Isman, Suci Madiarti; Fatawi, Izzul; Rustan, Dwi Rezki Hardianto Putra (Indonesian Research Journal in Education |IRJE|, 2025)
This research presents the design of a multidimensional profiling framework to support adaptive and personalized English language learning at Universitas Terbuka (UT). A qualitative research method was used in designing the profiling framework. Data were collected through focus group discussions (FGDs) and institutional observations to examine the current realities within the university. Thematic analysis was then employed to interpret the data. Two key results were a learner profiling framework and an institutional readiness mapping. The framework included four phases: (1) Input: collecting data on learners’ digital readiness, learning styles, English proficiency, and self-regulated learning; (2) Processing: analyzing the data to create learner profiles; (3) Adaptation: using profiles to suggest personalized support; and (4) Interpretation: presenting results through dashboards and feedback tools. The institutional mapping found that each phase required a clear governance structure to ensure ethical use, transparency, and alignment with Universitas Terbuka’s policies and stakeholder capacities.